Major trends in a future South Africa and some implications for intercultural communication in marketing - Clive Corder (Communicare)
It is now broadly accepted that long term shifts occur in the values that people hold which determine their behaviour. In the South African con text this process is being accelerated by the clash between Ideologies. It is argued that there is one megatrend in South Africa, namely Equality, which is leading to the development of parallel and reactionary sub-trends. In many respects South Africa is moving in the opposite direction to other developed countries, but it can not hide from certain global influ ences, in particular the gathering world-wide concern about Environmental Conservation. These deep seated changes, which, for the most part, reflect a conflict between the freedom of the individual and a de sire for uniformity, have considerable significance for communication and marketing.